The mysterious case of the C. elegans gut granule: death fluorescence, anthranilic acid and the kynurenine pathway - Gems, David; Coburn, Cassandra (Frontiers in Genetics, 2013)
Gut granules are lysosome-like organelles with acidic interiors that are found in large numbers within the intestine of the nematode Caenorhabditis elegans. They are particularly prominent when viewed under ultraviolet light, which causes them to emit intense blue fluorescence. Yet the function of these large and abundant organelles in this heavily-studied model organism remains unclear. One possibility is that they serve as storage organelles, for example of zinc. A new clue to gut granule function is the identification of the blue fluorescent material that they contain as a glycosylated form of anthranilic acid, which is derived from tryptophan by action of the kynurenine pathway. This compound can also serve a surprising role as a natural, endogenous marker of organismal death.